Interim report on an intensive study of the fish fauna of the Muskeg River watershed of northeastern Alberta ... - Machniak, K.; Bond, W. A. (University of Alberta Library, 1977)
The fish fauna of the Muskeg River was studied during spring and summer, 1976. Migrations of non-resident fish from the Athabasca River into the Muskeg River watershed were monitored through the use of a two-way counting fence between 28 April and 30 July. A total of 6153 fish were passed through the upstream trap of which white suckers (46%) and longnose suckers (46%) comprised the vast majority. Arctic grayling (5%) and northern pike (2%) accounted for most of the remainder. After spawning in the lower reaches of the Muskeg River, migrant suckers of both species returned to the Athabasca River. Arctic grayling, however, remained in the tributary throughout the summer. Floy tags applied to 2269 migrant fish yielded a 1.2% return rate for fish recaptured outside the Muskeg watershed. Small fish collections made throughout the summer demonstrated the importance of the lower Muskeg drainage as a rearing area for young of-the year white suckers, longnose suckers and Arctic grayling. Lake chub, slimy sculpin and ...